2021
DOI: 10.1002/jms.4727
|View full text |Cite
|
Sign up to set email alerts
|

Design of experiments for development and optimization of a liquid chromatography coupled to tandem mass spectrometry bioanalytical assay

Abstract: Design of experiments (DoE) is a valuable tool for the optimization of quantitative bioanalytical methods utilizing liquid chromatography coupled to tandem mass spectrometry (LC–MS/MS). Liquid chromatography mass spectrometry (LC–MS) is composed of several processes, including, liquid introduction and analyte ionization. The goal is to transfer analytes from atmospheric pressure to vacuum and maintain conditions that are compatible for both LC and MS. These processes involve many experimental factors which nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Initially, a full factorial design was carried out (DoE—Step 1), in which all variables, their interactions, and levels were considered in the calculations. This design allows the screening of a high number of factors with fewer experiments and can also be used for robustness or ruggedness testing ( Thorsteinsdóttir & Thorsteinsdóttir, 2021 ). To meet this end, three critical method parameters that mainly affect chromatographic selectivity were considered: 1) chemistry of the stationary phase (column); 2) type of organic modifier, and 3) pH values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, a full factorial design was carried out (DoE—Step 1), in which all variables, their interactions, and levels were considered in the calculations. This design allows the screening of a high number of factors with fewer experiments and can also be used for robustness or ruggedness testing ( Thorsteinsdóttir & Thorsteinsdóttir, 2021 ). To meet this end, three critical method parameters that mainly affect chromatographic selectivity were considered: 1) chemistry of the stationary phase (column); 2) type of organic modifier, and 3) pH values.…”
Section: Resultsmentioning
confidence: 99%
“…The disadvantage of this strategy relies on the increased number of experiments and longer development time, especially when many parameters are affecting the separation. To circumvent this, the use of the design of experiments (DoE) analytical approaches, which systematically vary multiple key variables (e.g., pH, temperature, organic modifier, stationary phase, among others) simultaneously to obtain suitable experimental conditions with a minimum number of experiments ( Tome et al, 2019 ; Thorsteinsdóttir & Thorsteinsdóttir, 2021 ). Screening and response-surface experimental designs allow the identification of significant factors, and the factor−response relationship is described by mathematical models, which can predict the optimal response.…”
Section: Introductionmentioning
confidence: 99%
“…Screening is used to detect significant factors that may influence the outcome, and to identify the limits in which they ought to be investigated. After screening, a blend of factors that can yield optimal working conditions in a process called optimization have to be identified (Benredouane et al., 2016 ; Mhango et al., 2017 ; Thorsteinsdóttir & Thorsteinsdóttir, 2021 ). MODDE ® 13 (Sartorius, Umeå, Sweden) was used to design the experiment and perform statistical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, Tabani et al reported that maltodextrin with low DE (4-7) has a higher degree of stereoselectivity compared to DE (13)(14)(15)(16)(17) and DE (16.5-19.5) [10]. Its high aqueous solubility and low absorbance in the UV region allow MD to be employed at relatively high additive concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Contour surface plots can be used to visualize how the response is affected by factors and to find combinations of optimal conditions. Optimal designs, such as D-optimal designs allows for the identification of the critical factors and an interaction between variables with maximal information and a minimum number of trials [ 15 ]. This approach reduces the analysis time and results in a more efficient experiment.…”
Section: Introductionmentioning
confidence: 99%